Insulin attenuates vasopressin-induced calcium transients and a voltage-dependent calcium response in rat vascular smooth muscle cells. - Standley, P R (1991)
Insulin attenuates the contractile responses of vascular smooth muscle (VSM) to various agonists. Insulinopenic and insulin-resistant rats lack this normal attenuation of vascular contractile responses. To study this attenuating mechanism, the effects of insulin on calcium (Ca2+) responses of cultured VSM cells (a7r5) to arginine vasopressin (AVP) and membrane potential were investigated. Insulin (1 and 100 mU/ml) shifted AVP dose-response curves to the right, reducing relative potency of AVP by 16-fold and 220-fold, respectively. Responses to AVP were significantly attenuated within 30 min of insulin application. The AVP-elicited rise in [Ca2+]i was partially dependent upon extracellular Ca2+. AVP-elicited inward current was reduced by 90 min of insulin treatment (100 mU/ml), from a peak current of -103 +/- 27 pA (normal) to -37 +/- 15 pA (insulin treated). Peak voltage-dependent Ca(2+)-dependent inward current was unaffected by insulin; however, the current-voltage curve was shifted 16 +/-3 mV to the right by insulin. Thus, insulin may reduce VSM contractile responses by attenuating agonist-mediated rises in [Ca2+]i mediated, in part, by reductions in Ca2+ influx through both receptor- and voltage-operated channels.